Play nice but win : a CEO's journey from founder to leader - Dell, Michael, 1965- (Portfolio, 2021)
"More than an honest portrait of a leader at a crossroads, Play Nice But Win is a survival story proving that while anyone with technological insight and entrepreneurial zeal might build something great-it takes a leader to build something that lasts"--